Management of Cesarean Scar Pregnancy: A Single-Institution Retrospective Review. (5th March 2018) - Giampaolino, P.; De Rosa, N.; Morra, I.; Bertrando, A.; Di Spiezio Sardo, A.; Zizolfi, B.; Ferrara, C.; Della Corte, L.; Bifulco, G.
Abstract : Objective . Cesarean scar pregnancy (CSP) is a rare condition that occurs when the pregnancy implants in a cesarean scar. An early diagnosis and a proper management are fundamental to prevent maternal complications. We review and discuss the different treatment employed in our unit to reduce morbidity, preserve fertility, and predict possible complications. Methods . The reported treatment has been expectant management, operative hysteroscopy approach, and intramuscular injection of 50 mg methotrexate (MTX), followed by cervical dilation and manual vacuum aspiration (D&S) with a Karman cannula under ultrasound guidance, uterine artery embolization (UAE), and manual vacuum aspiration under ultrasound guidance and uterine artery embolization before surgical laparotomic resection. Results . Complications were more frequent in women with a history of three or more cesarean section deliveries and with a myometrial thickness thinner than 2 mm. MTX and D&S treatment appear to be most effective and safe at the early age of pregnancy, while UAE and D&S are related to the highest risk of complication in any age of pregnancy. Conclusion . An appropriate preoperative diagnostic evaluation, the identification of cases at higher risk, and those eligible for a conservative treatment are fundamental to reduce complications.